2012
DOI: 10.1371/journal.pone.0050387
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Cytokine Correlates of Severe Dengue Infection

Abstract: BackgroundThe occurrence of dengue haemorrhagic fever (DHF) is thought to result from a complex interplay between the virus, host genetics and host immune factors. Existing published data are not consistent, in part related to relatively small sample sizes. We set out to determine possible associations between dengue virus (DEN-V) NS3 specific T cells and cytokine and chemokine levels and the pathogenesis of severe disease in a large cohort of individuals with DHF.Methodology/Principal FindingsBy using ex vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
92
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 44 publications
(51 reference statements)
11
92
2
3
Order By: Relevance
“…2A). The frequency of nonviable cells in children with dengue found here is consistent with previous reports that used propidium iodide and annexin V (29). The mechanisms by which DV induces cell death are not entirely clear and are dependent on the cellular type analyzed.…”
Section: Discussionsupporting
confidence: 89%
“…2A). The frequency of nonviable cells in children with dengue found here is consistent with previous reports that used propidium iodide and annexin V (29). The mechanisms by which DV induces cell death are not entirely clear and are dependent on the cellular type analyzed.…”
Section: Discussionsupporting
confidence: 89%
“…20,21 Both IL-10 and TNF-α are strongly associated with severe dengue infection. 22 The HIV-1 viral loads in our patient remained at normal levels (< 40 HIV-1 RNA copies/mL) during DENV-1 infection and 6 months later. Watt and others 8 have reported a reduction in the HIV-1 viral load in an HIV-1-positive patient without HAART treatment who presented with dengue infection in Thailand, and demonstrated that HIV-1 replication was suppressed during the acute phase of the infection.…”
Section: Discussionmentioning
confidence: 48%
“…They are known to play an important role in both acute [11] and chronic viral infections [14,28], including a recent report on their role in dengue infection [12]. Acute dengue is known to associate with a marked lymphopenia [29], especially with reduction of T cells due to massive T cell apoptosis [8,9]. We have also observed that DENV-specific IFN-g T cell responses are impaired during acute dengue, especially in those with more severe forms of dengue [7].…”
Section: Discussionmentioning
confidence: 53%
“…Our previous studies on T cell responses in acute dengue infection have shown that DENV-specific T cells have an impaired ability to produce cytokines such as interferon (IFN)-g and to degranulate [7]. In addition, T cells have been shown to undergo dramatic apoptosis in dengue infection [8,9]. Therefore, it would be crucial to examine the role of other immune cells that are capable of the rapid activation and production of large quantities of cytokines in the pathogenesis of acute dengue infection.…”
Section: Introductionmentioning
confidence: 99%